Economic and Environmental Energy Scheduling of Smart Hybrid Micro Grid Based on Demand Response - Harikumar Pallathadka,; Shavan Askar,; Ankur Kulshreshta,; M. K. Sharma,; Sabir Widatalla,; Mudae, I.S. (International Journal of Integrated Engineering, 2024)
Recently, microgrids are regarded as one of the main substations in distribution networks that generate electrical energy locally. The privileges of microgrids are easy management, optimization and highly reliable supply. In this paper, the recommended model is based on economic and emission optimal scheduling in connection to main grid mode, implementation model is as the short-term mode with optimal operation units and using real-time pricing (RTP) plan. In this study, multi objective function for operating cost and emission with augmented ?-constraint method has been considered and also fuzzy decision making process has been employed to obtain best solution. In addition, microgrid has interruptible and shiftable loads that can participate in demand response programs, that eventually the presented results have been evaluated based on demand response different programs.